Assessment of building design and overheating on occupants’ thermal comfort and energy performance considering self-build houses in a hot arid urban environment - Ouanes, Sara; Sriti, Leila; Khadraoui, Mohamed Amine (Technium Social Sciences Journal, 2022)
In recent years, energy conservation issues, environmental problems and their consequences on public health have increased interest in climatic responsive design to achieve better thermal comfort conditions inside the building without enhancing energy consumption. As people spend most of their time in interior spaces, indoor thermal conditions significantly impact their health and wellbeing. Extended exposure to extreme temperatures might cause heat-related illnesses, respiratory and cardiovascular diseases, or death. This paper evaluates the indoor thermal environment generated by the residential buildings’ fabric under overheating conditions. The study was conducted during the summer in a typical residential district in Biskra (Algeria). To assess the thermal response of the buildings’ fabric by taking into account the natural and social context of Biskra, as well as, the energy consumption behaviour of householders, a dynamic simulation study was performed over 115 self-build houses. The results showed that indoor thermal conditions in the analysed building were far from the optimum comfort air temperature except when using air conditioners. The most unfavourable conditions were reported in July and August when the air conditioners have to run full time to mitigate the effect of overheating. This implies that houses are poorly designed and failed to deal with overheating. To address with this issue, the residents are constrained to use air-conditioning most of the time to achieve thermal comfort which leads to increase in energy usage. Finally, despite the government reduced the cost of electricity and gas bills by 65% in southern provinces as a financial support for householders, serious problems of discomfort remain in the prevailing housing stock. Legislation and measures must be taken and enforced at provincial and local level regarding housing which should include energy efficiency and thermal comfort.